Feminism, Family, and Women's Rights: A Hermeneutic Realist Perspective - Browning, Don S. (Zygon, 2003)
In this article I apply the insights of hermeneutic realism to a practical-theological ethics that addresses the international crisis of families and women's rights. Hermeneutic realism affirms the hermeneutic philosophy of Hans-Georg Gadamer but enriches it with the dialectic of participation and distanciation developed by Paul Ricoeur. This approach finds a place for sciences such as evolutionary psychology within a hermeneutically informed ethic. It also points to a multidimensional model of practical reason that views it as implicitly or explicitly involving five levels—background metaphysical visions, some principle of obligation, assumptions about pervasive human tendencies and needs, assumptions about constraining social and natural environments, and assumed acceptable rules of conduct. The fruitfulness of this multidimensional view of practical reason is then demonstrated by applying it to practical-theological ethics and the analysis of four theorists of women's rights—Martha Nussbaum, Susan Moller Okin, Lisa Cahill, and Mary Ann Glendon. Finally, I illustrate the importance and limits of the visional dimension of practical reason by discussing the concept of “Africanity” in relation to the family and AIDS crisis of Eastern Africa.